Dynamic Detection of Monocyte Subsets in Peripheral Blood of Patients with Acute Hypertriglyceridemic Pancreatitis - Junyuan Zheng; Junjie Fan; Chunlan Huang; Yingying Lu; Zehua Huang; Xingpeng Wang; Yue Zeng (Gastroenterology Research and Practice)
Aim. Monocytes play an important role in acute pancreatitis (AP). Hypertriglyceridemic pancreatitis (HTGP) is always more severe than normal lipid-AP, whether the mechanism of aggravation involves monocyte subsets remains unknown though. The present study was aimed to analyze changes of peripheral blood M1 and M2 monocytes in HTGP patients. Methods. A total of 90 subjects were enrolled, among which 16 diagnosed with HTGP, 34 with acute biliary pancreatitis (ABP), 20 with hypertriglyceridemia (HTG), and 20 healthy controls (HC). Peripheral blood CD14+CD86+ M1 and CD14+CD206+ M2 monocytes were examined by flow cytometry on days 1, 3, and 7 after admission. Results. We found a marked increase in total and M1 monocyte count in AP patients (P<0.05). In HTGP, the percentage of M1 monocytes in white blood cells was significantly higher on days 1, 3, and 7, while M2 monocyte percentage was decreased on day 3, compared with ABP (P<0.05). In mild HTGP, M1 monocyte count and percentage gradually decreased, while M2 monocyte percentage gradually increased from day 1 to 7. In severe HTGP, M1 monocyte count and percentage rose to the highest point while M2 were the lowest on day 3. Additionally, the level of M1 monocytes showed a positive correlation with plasma triglyceride and Ranson score of HTGP patients. Conclusions. Peripheral blood M1 and M2 monocytes showed different dynamic changes in mild and severe HTGP. A more dominant role of CD14+CD86+ M1 monocytes may be involved in the pathogenesis of HTGP.